Prospecção in sílico de bilobalídeos, ginkgolídeos e seus derivados com potencial inibitório sobre a protease do SARS-COV-2: 3CLPRO (main protein) - Ribeiro, Francisca Jessica Penha (2023)
In 2019, a new pathology caused by the novel coronavirus SARS-CoV-2 was identified in the city of Wuhan in China. This pathology became known as COVID-19 and presents varied initial symptoms, commonly related to pneumonia and with a rapidly evolving picture and death. To date, more than 776 million people have been infected worldwide, and 6.87 million have lost their lives. In response to this threat, global efforts have been coordinated to develop effective vaccines and drugs. In this context, among the main therapeutic targets of SARS-Cov-2 is the major protease (3CLpro or Mpro), which is responsible for cleavage and activation of proteins required during viral replication. Despite efforts, pharmacological inhibition of these enzymes has proven challenging. In this work, we used computational-based drug development tools to identify new compounds with potential Mpro inhibitory activity by studying 2nd metabolites from Ginkgo biloba (ginkgolides and bilobalides) and their derivatives. To better assess the accessible chemical space in this therapeutic target, the inherent flexibility of this enzyme was explored using ensemble docking strategy, where a conformational assembly of this protein was used to characterize the interaction with the proposed compounds. Strategies of chemical space enlargement, analysis of pharmacokinetic properties, ease of synthesis, as well as interaction profiling with catalytic site residues will be extensively employed to generate a library of tested derivative compounds. Extended molecular dynamics techniques used to characterize their inhibition profile. With docking results, it was observed that the ligands were small to the site, so the best interaction energies of the bilobalides were BLBLD D1(-7.88), BLBLD D2 (-8.17), BLBLD D3 (-7.81), BLBLD D4 (-7.87), BLBLD D5 (-7.55), BLBLD D6 (-7.59), BLBLD SKL (-7.51) and BLBLD PNI (-7.83). For the ginkgolides the best energies were GINKGD1(-8.57), GINKGD 2 (-9.61), GINKGD 3(-9.29), GINKGD 4 (-8.56), GINKGD 5 (-9.29), GINKGD 6 (-9, 01), GINKGD 7 (-8.55), GINKGD 8 (-8.54), GINKGD 9 (-8.36), GINKGD 10 (-8.56), GINKGD 11 (-8.82), GINKGD 12 (-8.83), GINKGD 13 (-9.43) and GINKGD 14 (-8.52). Moving on to the derivation step using LigBuilder all ligands were submitted, but by selectivity of the software the ones that produced viable derivatives were from BLBLD D1 and BLBLD D2, generating 2003 molecules in total. These molecules were subjected to re-scoring with Vina and then to ADME to ascertain the pharmacokinetic properties with only the candidate derived from BLBLD D1 of cluster 1 ligand showing two violations of Lipinski rules, soon after the best candidates (C7L1, C62L2 and C72L4) were subjected to 300ns molecular dynamics. Therefore, C7L1 showed promising features to inhibit Mpro with interactions with the catalytic site and binding stability of the protein-binding complex. The results found will guide the rational design of new therapeutic agents inspired by nutraceuticals (natural products) and motivate the synthesis of promising compounds for in vitro and in vivo testing.